Method for introducing hydrogen for evaluating delay breakage characteristics and method for evaluating delay breakage characteristics of metal material
By electrically connecting metal materials and introducing potential difference into the electrolyte, the problem of limited hydrogen introduction position in the prior art is solved, and stable hydrogen introduction and delayed crack characteristics evaluation under the condition of no external power supply are achieved, and the evaluation process is simplified.
Patent Information
- Application Number
- JP2023121789
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2043-07-26
AI Technical Summary
The prior art requires the use of equipment such as constant current generators, which limits the introduction location of hydrogen in metal materials, and makes it difficult to easily evaluate its delayed crack characteristics without an external power supply.
By electrically connecting the metal material 1 and the metal material 2, immersing the electrical connection part into the electrolyte, hydrogen is introduced by using the potential difference between the electrodes, and hydrogen is introduced under the condition of no external power supply and evaluation of the delayed crack characteristics.
The stable and repeatable hydrogen introduction is achieved under the condition of no external power supply, simplifying the process of delayed crack characteristics evaluation and improving the reliability and efficiency of evaluation.
Smart Images

Figure 2025018245000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogen introduction method for evaluating delayed fracture properties and a method for evaluating the delayed fracture properties of metallic materials. [Background technology]
[0002] In recent years, the strength of steel materials used in various industrial fields has been increasing from the viewpoint of energy and resource conservation. The strength of steel sheets used in automobiles has also been increasing. For example, high-strength steel sheets with a tensile strength of over 1470 MPa are being used for automobile components.
[0003] However, delayed fracture may occur in high-strength steel materials. Delayed fracture is a phenomenon in which a metallic material undergoes sudden brittle fracture after a certain period of time has passed while it is subjected to a static load stress (a load stress below the tensile strength), with little or no apparent plastic deformation. Delayed fracture of steel is more likely to occur as its strength increases, and is particularly likely to occur in high-strength steel plates having a tensile strength of 1180 MPa or more.
[0004] Delayed fracture occurring in steel materials is influenced by, for example, residual stress remaining in the steel material when the steel material is formed into a predetermined shape by processing such as press working, and hydrogen embrittlement in the steel material at the concentrated portion where the residual stress is concentrated. In most cases, the hydrogen that causes hydrogen embrittlement is hydrogen that has infiltrated into the steel from the external environment and diffused therein (infiltrated hydrogen), such as hydrogen that is generated during corrosion of the steel and that has infiltrated into the steel and diffused therein.
[0005] Delayed fracture can also occur in metallic materials other than steel. In order to evaluate the delayed fracture properties of a metallic material, for example, hydrogen is introduced into the metallic material, and it is judged whether or not cracks occur in the metallic material depending on the amount of introduced hydrogen (amount of hydrogen penetration). An example of a method for introducing hydrogen into a metal material is the method described in Patent Document 1. That is, Patent Document 1 describes a method for introducing hydrogen into a test piece (metal material) by immersing an anode and a cathode in contact with the test piece in an electrolyte and then passing a constant current through the anode and the cathode. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2005-134152 A Summary of the Invention [Problem to be solved by the invention]
[0007] The method described in Patent Document 1 requires a constant current generating device such as a potentiostat, which increases the initial cost, and hydrogen can only be introduced into the metal material at locations with an external power source.
[0008] Therefore, an object of the present invention is to easily introduce hydrogen into a metallic material and evaluate the delayed fracture properties of the metallic material. [Means for solving the problem]
[0009] As a result of extensive investigations, the present inventors have found that the above object can be achieved by employing the following configuration, and have completed the present invention. That is, the present invention provides the following [1] to [6]. [1] A hydrogen introduction method for evaluating delayed fracture characteristics, comprising: a connection step of electrically connecting a metallic material 1 and a metallic material 2; and a hydrogen introduction step of immersing at least a portion of the surfaces of the electrically connected metallic material 1 and metallic material 2 in an electrolyte and introducing hydrogen into the metallic material 1, wherein an immersion potential E1 of the metallic material 1 is higher than an immersion potential E2 of the metallic material 2. [2] A method for evaluating the delayed fracture properties of a metallic material, comprising an evaluation step of evaluating the delayed fracture properties of the metallic material 1 into which hydrogen has been introduced using the method described in [1] above. [3] The method for evaluating the delayed fracture properties of a metallic material described in [2] above, wherein the metallic material 1 is the base material after removing the coating material from a coated metallic material in which the coating material is formed on the base material, or the base material before the coating material is formed, and the metallic material 2 is a metallic material containing the metal M constituting the coating material. [4] A method for evaluating the delayed fracture properties of a metallic material as described in [3] above, in which the coated metal material is a plated steel sheet in which a plating film is formed on a base steel sheet, the base material is the base steel sheet, and the coating material is the plating film. [5] A method for evaluating the delayed fracture properties of a metallic material according to any one of [2] to [4] above, in which the ratio S2 / S1, which is the ratio of the total area S2 of the surfaces of the metallic material 2 in contact with the electrolyte to the total area S1 of the surfaces of the metallic material 1 in contact with the electrolyte, is 1.0 or more. [6] The method for evaluating delayed fracture properties of a metallic material according to any one of the above [2] to [5], wherein the electrical conductivity of the electrolytic solution is 2.0 mS / cm or more. Effect of the Invention
[0010] According to the present invention, hydrogen can be easily introduced into a metallic material, and the delayed fracture properties of the metallic material can be evaluated. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic diagram showing a hydrogen introduction device. [Diagram 2] FIG. 2 is a schematic diagram showing another hydrogen introduction device. [Diagram 3] 1(a) to 1(c) are perspective views showing a procedure for preparing a bending test piece. [Figure 4] 1(a) and 1(b) are plan views showing a procedure for preparing a tensile test piece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] [Method of hydrogen introduction for evaluating delayed fracture properties and method of evaluating delayed fracture properties of metallic materials] The hydrogen introduction method for evaluating delayed fracture properties in this embodiment includes a connection step of electrically connecting metallic material 1 and metallic material 2, and a hydrogen introduction step of immersing at least a portion of the surfaces of the electrically connected metallic material 1 and metallic material 2 in an electrolyte and introducing hydrogen into metallic material 1, wherein the immersion potential E1 of metallic material 1 is higher than the immersion potential E2 of metallic material 2 (the immersion potential E1 is more noble than the immersion potential E2).
[0013] The method for evaluating the delayed fracture properties of a metallic material of this embodiment also includes an evaluation step of evaluating the delayed fracture properties of the metallic material 1 into which hydrogen has been introduced using the hydrogen introduction method for evaluating delayed fracture properties of this embodiment.
[0014] This embodiment will be described in more detail below. The following description will be directed to both the hydrogen introduction method for evaluating delayed fracture properties and the method for evaluating delayed fracture properties of metallic materials.
[0015] <Hydrogen introduction device> First, an apparatus (hydrogen introducing apparatus) used when introducing hydrogen into the metal material 1 will be described with reference to FIGS. 1 is a schematic diagram showing a hydrogen introduction device 6. The device includes a metal material 1, a metal material 2, a conducting wire 3 electrically connecting the metal material 1 and the metal material 2, and an electrolytic cell 4 containing an electrolytic solution 5. As shown in FIG. 1, at least a portion of a surface of the metal material 1 is immersed in the electrolytic solution 5, and at least a portion of a surface of the metal material 2 is immersed in the electrolytic solution 5. The number of the metal material 1 and the metal material 2 may be two or more, instead of one.
[0016] Fig. 2 is a schematic diagram showing another hydrogen introduction device 7. Fig. 2 shows two metal materials 1 (metal material 1a and metal material 1b). That is, one metal material 1a is connected to metal material 2 by a conductor 3a, and the other metal material 1b is connected to metal material 2 by a conductor 3b.
[0017] <Connection steps> In the connecting step, metal material 1 and metal material 2 are electrically connected. An example of a method for electrically connecting the metal material 1 and the metal material 2 is a method for connecting the metal material 1 and the metal material 2 using a conductor. The conductor may be, for example, a copper wire, and a commercially available product may be used. Methods for connecting a conductor to a metal material (metal material 1 or metal material 2) include, for example, a method of clamping the conductor to the metal material using a clip such as an alligator clip; a method of soldering the conductor to the metal material; a method of clamping the metal material with an alligator clip to which a conductor is connected; and the like.
[0018] <Hydrogen introduction step> In the hydrogen introduction step, at least a portion of the surfaces of the electrically connected metal material 1 and metal material 2 is immersed in an electrolyte, and hydrogen is introduced into the metal material 1.
[0019] <Immersion potential E1 and immersion potential E2> In the present embodiment, in the electrolyte used, the immersion potential E1 of the metal material 1 is higher than the immersion potential E2 of the metal material 2 (E1>E2). In this embodiment, by using this potential difference, hydrogen can be easily introduced into the metal material 1 without using an external power source. Specifically, with the potential difference (E1-E2) as the driving force, a dissolution reaction (anodic reaction) of the metallic material 2 occurs on the surface (immersed surface s2) where the metallic material 2 comes into contact with the electrolyte, and a hydrogen generation reaction (cathodic reaction) occurs on the surface (immersed surface s1) where the metallic material 1 comes into contact with the electrolyte. In this way, hydrogen is introduced into the metallic material 1 in a stable manner.
[0020] More specifically, hydrogen gas (H2) is produced by the cathode reaction, but it is believed that hydrogen atoms are produced as a preliminary step, and some of these are dissolved in the metal (e.g., Fe) that constitutes the metallic material 1. In other words, most of the hydrogen is discharged to the outside of the system as hydrogen gas, but some is introduced into the metallic material 1 and gradually diffuses from the surface of the metallic material 1 to the inside.
[0021] As long as the elements that make up the metal materials (metal material 1 and metal material 2) do not change to other elements along the way, the potential difference (E1-E2) will remain constant. If the potential difference is constant, the current value will also be constant, and the hydrogen generation reaction that occurs in that case will also be constant and reproducible. This is what is meant by "stable." Generally, various evaluation tests require reproducibility, but according to this embodiment, the introduction of hydrogen into the metallic material 1 is stable and reproducible. Therefore, this embodiment is suitably used for evaluating delayed fracture properties.
[0022] Evaluation Steps In the evaluation step, the delayed fracture properties of the metal material 1 into which hydrogen has been introduced are evaluated. For example, the delayed fracture properties of the metallic material 1 are evaluated based on the time until cracks occur in the metallic material 1 due to the introduction of hydrogen, the amount of hydrogen, the stress, and the like. Specifically, for example, the delayed fracture properties of the metallic material 1 are evaluated as follows.
[0023] A stress is applied to the metallic material 1 to form a stress-applied portion. Hydrogen is introduced into the metallic material 1 with the stress-applied portion formed therein. At this time, the conditions for introducing hydrogen (amount of hydrogen) are changed, and the delayed fracture properties of the metallic material 1 are evaluated based on the amount of hydrogen at which cracks occur in the metallic material 1. A stress-applied portion is formed by processing, and a predetermined amount (constant amount) of hydrogen is introduced into a plurality of metal materials 1 each having a different stress in the stress-applied portion, and the delayed fracture properties are evaluated based on the stress in the stress-applied portion at which a crack occurs. Hydrogen is introduced into the metal material 1 that does not form a stress-applied portion, and after the introduction of hydrogen, stress is applied, and the delayed fracture properties are evaluated based on the stress at which cracks occur. A load is applied to the flat metal material 1 while hydrogen is being introduced, and the delayed fracture properties are evaluated based on the load at which cracks occur. A predetermined amount (constant amount) of hydrogen is introduced into the metal material 1 forming the stress-loaded portion, and the delayed fracture properties are evaluated based on the time required for cracks to occur.
[0024] Examples of methods for forming a stress applying portion in a metal material include bending, stretching, drawing, shearing, welding, and the like. Examples of bending processes include hat-shaped bending, U-shaped bending, V-shaped bending, etc. U-shaped and V-shaped bending are simpler than hat-shaped bending, and the load stress on the bent portion can be changed by adjusting the tightening amount using a bolt. Automotive parts are often manufactured by bending, shearing and / or welding. Therefore, when evaluating the delayed fracture properties of a metal material used as an automotive part, it is preferable to form a stress-loaded part by bending, shearing and / or welding the metal material. Before forming the stress-loaded part, strain (plastic deformation) may be imparted by rolling, tensile processing or the like.
[0025] <Electrolyte> The electrolyte is composed of a solute and a solvent, and has the function of passing a current (galvanic current) based on the potential difference between the metallic material 1 and the metallic material 2. The electrolyte is not particularly limited as long as it allows a galvanic current to flow. However, if the conductivity of the electrolyte is too low, the galvanic current does not flow easily, and the hydrogen generation reaction in the metal material 1 may not proceed stably. Therefore, from the viewpoint of efficiently passing a galvanic current between the metal material 1 and the metal material 2, the conductivity of the electrolyte is preferably 2.0 mS / cm or more, more preferably 3.5 mS / cm or more, further preferably 7.0 mS / cm or more, and particularly preferably 10.0 mS / cm or more.
[0026] The upper limit of the electrical conductivity of the electrolyte is not particularly limited. However, since the effect becomes saturated, the conductivity of the electrolyte is, for example, preferably 100.0 mS / cm or less, and more preferably 50.0 mS / cm or less.
[0027] The solvent constituting the electrolytic solution is not particularly limited as long as it can pass a galvanic current and dissolve the electrolyte, but water is preferred from the viewpoint of causing the hydrogen generation reaction, which is the cathode reaction.
[0028] Examples of solutes constituting the electrolyte include chlorides (hydrochloric acid, sodium chloride, etc.) that promote the dissolution reaction (anode reaction) of the metal material 2; acidic or alkaline substances that adjust the pH; thiosulfate compounds (ammonium thiosulfate, etc.) that promote the introduction of hydrogen; and the like. These may be used alone or in combination of two or more.
[0029] <Area ratio (S2 / S1)> The area ratio (S2 / S1) is the ratio of the total area S2 of the surface (immersed surface s2) of metal material 2 in contact with the electrolyte to the total area S1 of the surface (immersed surface s1) of metal material 1 in contact with the electrolyte.
[0030] If the area ratio (S2 / S1) is too small, the dissolution reaction of the metal material 2 becomes the rate-limiting reaction (rate-limiting process), and the hydrogen generation reaction on the immersion surface s1 of the metal material 1 may not proceed sufficiently. In this case, the amount of hydrogen introduced into the metal material 1 is small. Therefore, from the viewpoint of allowing the hydrogen generation reaction to proceed sufficiently, the area ratio (S2 / S1) is preferably 1.0 or more, and more preferably 2.0 or more.
[0031] The upper limit of the area ratio (S2 / S1) is not particularly limited. However, if the area ratio (S2 / S1) is too large, it becomes necessary to enlarge the electrolytic cell and prepare a large amount of electrolyte, which may be disadvantageous in terms of workability and cost. For this reason, the area ratio (S2 / S1) is preferably equal to or less than 20.0, and more preferably equal to or less than 15.0.
[0032] The area ratio (S2 / S1) is adjusted, for example, by changing the size of the metal materials (metal material 1 and metal material 2). Specifically, for example, one method for increasing the area ratio (S2 / S1) is to connect a plurality of metal materials 2 to a metal material 1 to increase the total area S2 of the metal materials 2.
[0033] When the metal materials (metal material 1 and metal material 2) are coated metal materials such as plated steel sheets, they have surfaces of different metal types. In this case, when adjusting the area ratio (S2 / S1), it is preferable to coat the surfaces of the metal types that are not the evaluation target with resin or the like. At this time, it is preferable that the connection points between the conducting wires and the metal materials (metal material 1 and metal material 2) are located in positions that are not immersed in the electrolyte, or are covered with resin or the like.
[0034] As described above, an anodic reaction occurs on the immersion surface s2 of the metal material 2. For this reason, if a strong oxide film exists on the surface of the metal material 2, a stable anodic reaction may not occur easily. In such a case, it is preferable to mechanically or electrically remove the oxide film on the surface of the metal material 2.
[0035] <Metal materials> The shapes of the metal material 1 and the metal material 2 are not particularly limited, and as described above, a stress application portion may be formed.
[0036] As the metallic material 1, a metallic material (for example, a steel material) for which delayed fracture properties are to be evaluated is used. As described above, the higher the strength of a steel material, the more likely it is that delayed fracture will occur. Therefore, it is preferable to use, as the metallic material 1, a high-strength steel plate having a tensile strength of 1180 MPa or more.
[0037] The combination of the metallic material 1 and the metallic material 2 is not particularly limited as long as the immersion potential E1 of the metallic material 1 is higher than the immersion potential E2 of the metallic material 2. For example, when a steel plate is used as the metal material 1, a metal material having a lower immersion potential than the steel plate, such as zinc; an alloy of zinc and other elements; aluminum; an alloy of aluminum and other elements; or the like, is used as the metal material 2. However, depending on, for example, the oxidation state of the metal material, the content of other elements in the metal material, the conditions of the electrolyte (composition, temperature, etc.), etc., the immersion potential may be more noble than that of the steel sheet. Therefore, it is preferable to confirm in advance that E1>E2 in the electrolyte to be used. The immersion potential may be read from a potential-pH diagram, or may be actually measured in advance using a potentiostat or the like.
[0038] The metal material may be a coated metal material in which a coating material is formed on a base material. A specific example of a coated metal material is a plated steel sheet in which a plated film (coating material) is formed on a base steel sheet (base material).
[0039] The present inventors have conducted extensive research into the corrosion of plated steel sheets, and have found that corrosion of a plated coating (e.g., a zinc plated coating) progresses in the early stages, then the underlying steel sheet is partially exposed, galvanic corrosion progresses between the plated coating and the underlying steel sheet, and then corrosion of the underlying steel sheet progresses; that in plated steel sheets, hydrogen introduction due to galvanic corrosion has the greatest effect on delayed fracture properties; and
[0040] In other words, it was discovered that simulating the introduction of hydrogen due to galvanic corrosion between the plating film and the base steel sheet, introducing hydrogen into the base steel sheet, and evaluating the delayed fracture properties of the base steel sheet is important in accurately evaluating the delayed fracture properties of plated steel sheet.
[0041] Based on this finding, the inventors came up with the idea of using a base material (e.g., a base steel plate) of a coated metal material (e.g., a plated steel plate) as metal material 1, and using a coating material (e.g., a plating film) of the coated metal material as metal material 2. Hereinafter, a plated steel sheet will be described as an example of a coated metal material, but the present invention is not limited to this.
[0042] Specifically, as the metal material 1, it is preferable to use a base steel sheet obtained by removing the plating film from a plated steel sheet. The method for removing the plating film is not particularly limited, and examples thereof include a method in which the plated steel sheet is immersed in an acid or alkali depending on the components of the plating film to dissolve and remove the plating film (chemical treatment); a method in which the plating film is mechanically removed by polishing, grinding, or the like (mechanical treatment); and the like. Note that a base steel sheet before the formation of a plating film may be used as the metallic material 1. This eliminates the effect on the delayed fracture properties of the change in the surface condition of the base steel sheet caused by the removal of the plating film, and allows for a more accurate evaluation of the delayed fracture properties.
[0043] It is preferable to use a metal material containing metal M constituting the plating film as the metal material 2. Specifically, metal M is, for example, a metal that occupies 95 mass % or more (preferably 98 mass % or more) of the plating film. In other words, metal material 2 is not constituted by impurities (unavoidable impurities) contained in the plating film. When the metal M constituting the plating film is an alloy, it is preferable that the composition ratio (alloy ratio) of the metal M be reflected in the metal material 2 as well. The content of the metal M in the metal material 2 is preferably 96 mass % or more, and more preferably 98 mass % or more.
[0044] The metal material 2 may be a test piece in which only the plating film surface of a plated steel sheet is exposed (the base steel sheet is covered with a resin or the like). In this case, if the plating film is thin, there is a possibility that the plating film will disappear (dissolve) during the hydrogen introduction step, exposing the underlying steel sheet, and therefore it is preferable to use a plated steel sheet having a plating film of sufficient thickness. In addition, a plurality of test pieces may be prepared, and when the plating film of one test piece disappears, the test piece may be connected to the metal material 1 of another test piece.
[0045] The metal material 2 may be a metal plate obtained by melting and solidifying a metal so as to have the same composition ratio as the metal M constituting the plating film. When the plating film is a hot-dip plating film, a test piece prepared by solidifying a plating bath for forming the plating film may be used as the metallic material 2. When the plating film is an electroplating film, a test piece prepared by electrodepositing a metal M constituting the plating film may be used as the metal material 2. EXAMPLES
[0046] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the examples described below.
[0047] <Plated steel sheets A, B and C> Plated steel sheets A, B and C (sheet thickness: 1.6 mm) shown in Table 1 below were prepared as coated metal materials (plated steel sheets) comprising a base steel sheet and a plating film formed on the base steel sheet.
[0048] [Table 1]
[0049] <Metal materials A-1~C-3> Metal materials A-1 to C-3 to be used as the metal material 1 were prepared. First, the above-mentioned plated steel sheets A, B and C were used as they were to prepare metal materials A-1, B-1 and C-1, respectively, as shown in Table 2 below.
[0050] Next, the plated steel sheets were subjected to a chemical treatment to remove the plating film, thereby obtaining metal materials A-2, B-2 and C-2 made of base steel sheets, as shown in Table 2 below. The chemical treatment involved immersing the plated steel sheet in a 5% by mass aqueous solution of hydrochloric acid containing an inhibitor (Hibiron, manufactured by Sugimura Chemical Industry Co., Ltd.) to dissolve the plated film. After removing the plated film, the base steel sheet was immersed in a saturated aqueous solution of sodium bicarbonate to neutralize the acid components remaining on the surface of the base steel sheet, and then washed with water and dried.
[0051] Furthermore, the plated steel sheets were mechanically treated to remove the plating film, thereby obtaining metal materials A-3, B-3 and C-3 made of base steel sheets, as shown in Table 2 below. The mechanical treatment involved removing the plating film by surface grinding using a grindstone with a grit size of #220.
[0052] [Table 2]
[0053] Metal materials D and E to be used as metal material 2 were prepared. As metal material D, a zinc plate (Zn content: 99.9 mass %) was used, and as metal material E, an aluminum plate (Al content: 99.0 mass %) was used.
[0054] <Processing (forming the stress-applied portion)> Metal material 1 (more specifically, metal materials A-1 to C-3 used as metal material 1) was subjected to bending or tensile processing as described below to produce bending test pieces or tensile test pieces with stress-loaded portions formed.
[0055] 3(a) to 3(c) are perspective views showing the procedure for producing a bending test piece. First, the metal material 1 was sheared to a size of 35 mm in width and 100 mm in length, and then two holes 11 with a diameter of 10 mm were formed in the metal material 1 as shown in Fig. 3(a). After that, in order to remove the residual stress caused by the shearing, the metal material 1 was ground until its width became 30 mm. Next, after ultrasonic cleaning in toluene for 5 minutes, the metal material 1 was bent as shown in Fig. 3(b). Specifically, the metal material 1 was placed between the die and the punch so that the fracture surface of the sheared end face 12 of the metal material 1 faced the die and the sheared surface of the sheared end face 12 faced the punch, and was bent 180° with a curvature radius R of 5 mm. In this way, a bending test piece having a stress application portion 13 formed thereon was produced, as shown in Fig. 3(c). The bending test piece was restrained using a bolt 14 and a nut 15. At this time, the inner interval of the bending test piece was adjusted in the range of 10 to 20 mm, and the stress applied to the stress application portion 13 was changed in the range of 300 to 1700 MPa. The narrower the inner interval of the bending test piece, the higher the stress applied to the stress application portion 13.
[0056] 4(a) and 4(b) are plan views showing the procedure for preparing a tensile test piece. First, as shown in Fig. 4(a), the metal material 1 was sheared to a size of 35 mm in width × 100 mm in length. Then, in order to remove residual stress caused by shearing, the metal material 1 was ground until its width became 30 mm. Then, the central portion 21 of the metal material 1 was ground under the condition of a curvature radius R of 12.5 mm so that the central portion 21 had a size of 12 mm in length × 5 mm in width. Next, as shown in Fig. 4(b), the metal material 1 was subjected to tensile processing to prepare a tensile test piece having a stress application part 22. At this time, the stress applied to the stress application part 22 was changed in the range of 500 to 1400 MPa.
[0057] <Electrolyte> Pure water was used as the solvent for the electrolyte. The solutes used in the electrolyte were sodium chloride (NaCl), hydrochloric acid (HCl), and ammonium thiocyanate (NH4SCN). An electrolyte solution was prepared by dissolving one or two types of solute in a solvent at the concentration (unit: mass %) shown in Table 3 below. The conductivity (unit: mS / cm) of the electrolyte solution is shown in Table 3 below.
[0058] Connection and hydrogen introduction A commercially available vinyl-coated copper wire (conductor) was soldered to metallic material 1 and metallic material 2 to connect them together. Next, the connected metallic material 1 (more specifically, the stress-applied portion of metallic material 1) and metallic material 2 were immersed in an electrolyte, and hydrogen was introduced into metallic material 1.
[0059] Metallic Materials 1 and Metallic Materials 2 The metal materials 1 and 2 used are shown in Table 3 below. Specifically, when evaluating the delayed fracture properties of plated steel sheet A (plating film: Zn), metal materials A-2 to A-3 were used as metal material 1, and metal material D (metal type: Zn) was used as metal material 2. When evaluating the delayed fracture properties of plated steel sheet B (plating film: Al), metal materials B-2 to B-3 were used as metal material 1, and metal material E (metal type: Al) was used as metal material 2. When evaluating the delayed fracture properties of plated steel sheet C (plating film: Zn), metal materials C-2 to C-3 were used as metal material 1, and metal material D (metal type: Zn) was used as metal material 2.
[0060] However, in Nos. 1 to 3, metal materials A-1, B-1 and C-1 were used as metal material 1, and metal material 2 was not used. In Nos. 4 to 6, metal materials A-1, B-1 and C-1 were used as metal material 1, and the same metal materials A-1, B-1 and C-1 as metal material 1 were used as metal material 2. In Nos. 34 to 36, metal material D and metal material E were used interchangeably.
[0061] A bending test piece or a tensile test piece with a stress-applied portion formed thereon was used as the metal material 1. When a bending test piece was used, "bending" was recorded in the "Processing" column of Table 3 below, and when a tensile test piece was used, "tensile" was recorded in the "Processing" column of Table 3 below. In addition, the size and number of metal materials 1 and / or metal materials 2 were adjusted so as to obtain the area ratio (S2 / S1) shown in Table 3 below. Furthermore, in Table 3 below, the immersion potential E1 (unit: V vs. SHE) of metal material 1 and the immersion potential E2 (unit: V vs. SHE) of metal material 2 are shown.
[0062] Evaluation of delayed fracture properties Hydrogen was introduced into metallic material 1 to cause cracks to occur in the stress-applied portion of metallic material 1, and the delayed fracture properties were evaluated. The minimum stress at which cracks occurred among the stresses in the stress-applied portion is shown in Table 3 below as the lower crack occurrence stress (unit: MPa). If no cracks occurred, a "-" was entered.
[0063] It can be evaluated that the higher the value of the lower limit stress for crack generation, the less likely delayed fracture is to occur. Regarding the plated steel sheets A, B and C, it had been previously confirmed through a separate test that plated steel sheet C was most susceptible to delayed fracture, and plated steel sheet A was least susceptible to delayed fracture. Therefore, if the value of the lower limit stress for crack generation is A>B>C, it can be determined that the delayed fracture properties have been properly evaluated.
[0064] [Table 3] TIFF2025018245000005.tif228125
[0065] <Summary of evaluation results> As shown in Table 3 above, in Nos. 7 to 21 and 25 to 30, the order of the minimum stress for crack generation was A>B>C, and the delayed fracture properties could be properly evaluated.
[0066] In contrast, in Nos. 1 to 3 in which no metallic material 2 was used, in some cases no cracks were generated in the metallic material 1, and the delayed fracture properties could not be properly evaluated.
[0067] In Nos. 4 to 6, in which the same metal materials A-1, B-1 and C-1 as metal material 1 were used as metal material 2 (i.e., E1 = E2), in some cases no cracks occurred in metal material 1, and the delayed fracture properties could not be properly evaluated.
[0068] In Nos. 22 to 24, in which the electrical conductivity of the electrolyte was 1.2 mS / cm, no cracks were generated in the metallic material 1, and the delayed fracture properties could not be properly evaluated.
[0069] In Nos. 31 to 33, in which the area ratio (S2 / S1) was 0.5, in some cases no cracks were generated in the metallic material 1, and the delayed fracture properties could not be properly evaluated.
[0070] In Nos. 34 to 36, in which metallic material D and metallic material E were used interchangeably, the order of the minimum stress for crack generation was not A>B>C, and the delayed fracture properties could not be properly evaluated. [Explanation of symbols]
[0071] 1: Metal material 2: Metal material 3: Conductor 4: Electrolytic cell 5: Electrolyte 6: Hydrogen introduction device 7: Hydrogen introduction device 11: Hole 12: Sheared end face 13: Stress load section 14: Bolt 15: Nut 21: Central part 22: Stress load section
Claims
1. a connecting step of electrically connecting the metal material 1 and the metal material 2; A hydrogen introduction step of immersing at least a part of the surfaces of the electrically connected metal material 1 and the metal material 2 in an electrolytic solution and introducing hydrogen into the metal material 1, A hydrogen introduction method for evaluating delayed fracture properties, wherein an immersion potential E1 of the metallic material 1 is higher than an immersion potential E2 of the metallic material 2.
2. A method for evaluating the delayed fracture properties of a metallic material, comprising an evaluation step of evaluating the delayed fracture properties of the metallic material 1 into which hydrogen has been introduced using the method according to claim 1.
3. The metal material 1 is a base material after removing a coating material from a coated metal material in which a coating material is formed on a base material, or the base material before the coating material is formed, 3. The method for evaluating delayed fracture properties of a metallic material according to claim 2, wherein the metallic material 2 is a metallic material containing a metal M constituting the coating material.
4. The coated metal material is a plated steel sheet having a plating film formed on a base steel sheet, The base material is the base steel sheet, The method for evaluating delayed fracture properties of a metallic material according to claim 3 , wherein the coating material is the plating film.
5. The method for evaluating delayed fracture properties of a metallic material according to any one of claims 2 to 4, wherein S2 / S1, which is a ratio of a total area S2 of a surface of the metallic material 2 in contact with the electrolytic solution to a total area S1 of a surface of the metallic material 1 in contact with the electrolytic solution, is 1.0 or more.
6. The method for evaluating delayed fracture properties of a metallic material according to any one of claims 2 to 4, wherein the electrical conductivity of the electrolytic solution is 2.0 mS / cm or more.
Citation Information
Patent Citations
Cover inspecting method
JP1992329349A
Evaluation method of delayed breaking resistance of high-strength steel sheet
JP2007198895A
Hydrogen filling method and hydrogen embrittlement characteristic evaluation method
JP2019184585A
Zinc-coated steel sheet
WO2021241338A1
System for evaluating hydrogen embrittlement of thin sheet steel and its evaluation method
JP2005134152A